The effect of subjective exercise experience on anxiety disorder in university freshmen: the chain-mediated role of self-efficacy and interpersonal relationship - Xiang, Jun; Gao, Jia; Gao, Yun (Frontiers in Psychology, 2024)
Background Anxiety disorder is a significant concern in the context of mental health among university students. This study aimed to examine the impact of subjective exercise experience on anxiety disorder in freshmen and verify the mediating role of self-efficacy and interpersonal relationships between them. Methods A total of 1,308 Chinese freshmen underwent an investigation using the Subjective Exercise Experience Scale (SEES), Generalized Anxiety Disorder Scale (GAD-7), General Self-Efficacy Scale (GSES), and Interpersonal Relationship Comprehensive Diagnostic Scale (IRIDS). Results The outcomes of this study are as follows: (1) Boys exhibited marginally greater performance in physical activity assessments compared to girls while displaying somewhat lower scores than girls in measures of anxiety disorders, self-efficacy, and interpersonal relationship tests. Of these, 63.39% were diagnosed with mild anxiety, 51.73% were diagnosed with moderate anxiety, and 10% were diagnosed with severe anxiety; (2) The subjective exercise experience had a significant negative correlation with an anxiety disorder (r = −0.36, p < 0.01), and the subjective exercise experience had a direct negative impact on anxiety disorder (β = −0.112, t = −11.776, p < 0.01). Furthermore, subjective exercise experience positively predicted self-efficacy (β = 0.125, t = 13.236, p < 0.01) and interpersonal relationship (β = 0.395, t = 12.359, p < 0.01). Self-efficacy had a substantial impact on interpersonal relationships (β = 0.724, t = 12.172, p < 0.01) and anxiety disorders (β = −0.148, t = −8.387, p < 0.01). Interpersonal relationships had a significant positive predictive effect on anxiety disorder (β = −0.081, t = −10.441, p < 0.01); (3) Self-efficacy and interpersonal relationships were identified as important mediators between subjective exercise experience and anxiety disorder. The intermediary effect accounted for 18.84% of the total effect. Specifically, subjective exercise had a direct impact on anxiety disorders through self-efficacy mediators (2.90%), interpersonal mediators (1.45%), and self-efficacy and interpersonal chain mediators (14.49%). Conclusion Subjective exercise experience has a significant positive predictive effect on university students’ self-efficacy, interpersonal relationships, and anxiety disorder. Moreover, self-efficacy and interpersonal interactions serve as intermediaries between subjective exercise experiences and anxiety disorders. These findings have immense importance in advancing the mental well-being of freshmen and serve as a theoretical foundation for formulating intervention strategies. However, the study had certain limitations, such as the specificity of the sample and the use of self-reported data. Further research could enhance the sample size and utilize various assessment techniques to validate these findings.